Successful endovascular therapy for acute basilar thrombosis in an adolescent. - Kirton, A; Wong, J; Mah, J; Ross, B; Kennedy, J; Bell, K; Hill, MD (2003)
Pediatric stroke is an underrecognized, potentially treatable cause of childhood neurologic disease. Acute basilar artery thrombosis is a devastating disease rarely encountered in children. Acute interventions with both chemical and mechanical thrombolysis techniques can improve outcomes in adults with arterial thrombosis of the posterior cerebral circulation. We report a case of intervention with both intra-arterial alteplase (tissue plasminogen activator) and cerebral balloon angioplasty to treat a prolonged basilar artery occlusion secondary to idiopathic thrombosis in an adolescent. Despite the patient being clinically locked-in and intervention being delayed at least 20 hours from symptom onset, he obtained complete neurologic recovery. Issues of pediatric stroke, late therapeutic intervention, chemical thrombolysis, and cerebral angioplasty are discussed. This case highlights the underrecognition and subsequent delay in diagnosis of pediatric stroke and how acute intervention may cure otherwise catastrophic strokes in children.